A study of the relationship between corporate governance and firm performance : the case of Malaysia listed firms / Siti Nor Hidayu Mohamed Sukri - Mohamed Sukri, Siti Nor Hidayu (2012)
Corporate governance is a fairly new concept which has been put into practice because of the needs of companies to constantly perform better; and this is need that has made corporate governance so necessary today. As a set of limitations which must be adhered to in order for a company or firm to reach its optimal performance, corporate governance is a process which ensures growth for a firm and the economy. The globalisation of banking and financial markets has raised important issues regarding corporate governance regulation for banking and finance institutions. This paper examine the relationship between three important corporate governance mechanisms (board composition, board size and CEO status) and firm performance measures (return on assets, ROA), for a sample of 15 Malaysian listed firms between 2007 and 2011. The results provide evidence of a positive significant relationship between ROA and two corporate governance mechanisms (board size and CEO status). The study, however, could not provide a significant relationship between the firms performance measure (ROA) and board composition. Statistical Package for the Social Science (SPSS) was used to analyze the data. That is to examine the relationship between dependent and independent variables. To analyze this study, researcher used both of simple and multiple linear regression